Effect of Relative Isometric Strength on Countermovement Jump Performance in Professional and Semi-Professional Soccer Players - Nicholas Joel Ripley; Jack Fahey; Nabil Hassim; Paul Comfort (Biomechanics, 2025)
As powerful actions commonly proceed goal scoring opportunities within soccer, enhancing powerful actions could be essential to optimize performance. There is a large body of evidence supporting the positive associations between maximal isometric mid-thigh pull force-generating qualities and jump performance. Objectives: The purpose of this study was to determine if relative maximal isometric force production can discriminate between higher- and lower-performing jumpers among professional and semi-professional soccer players. As such, it was hypothesized that stronger players would have a greater jump performance than weaker players. Methods: An observational cross-sectional research design was used to assess ballistic and isometric force production of the lower limbs across players from four professional and semi-professional soccer clubs during the pre-season period. Seventy-six professional male lower-league soccer players (mass: 82.5 ± 8.2 kg; height: 1.80 ± 0.07 m; age: 25.8 ± 4.3 years) performed three trials of the countermovement jump (CMJ) and isometric mid-thigh pull (IMTP) using force plates. Players were categorized as strong and weak using the group’s average IMTP relative peak force (33.41 N/kg). A series of one-way Bayesian independent t-tests were performed to determine the difference between strong and weak groups. Results: A large magnitude of difference was observed between strong and weak players for relative peak force (d [95% CI] = 2.53 [2.017–∞]), with strong evidence supporting the hypothesis (BF10 = 2.698 × 10+14). There was moderate evidence to support the hypothesis that strong players (n = 37) had a greater modified reactive strength index (mRSI) and relative average braking force in comparison to weaker players (n = 39). All other evidence was weak, with trivial-to-small differences (d = 0.10–0.42) for jump height, jump momentum, propulsive force, force at minimum displacement, time to take off, and countermovement depth. Conclusions: Maximal relative strength has implications on jump performance, albeit not on the jump outcome. Stronger players performed the CMJ more efficiently when observing the mRSI, with a shorter time to take off, while producing greater average relative forces during the braking phase. This could have potential implications in the sporting environment when performing jumping tasks, where they can achieve a similar outcome over a shorter duration.